Copyright Protection for Works Created by AI Technology under the EU Law and Vietnamese Law - Le Thi, Minh (Review of European and Comparative Law, 2023)
The legislation of the European Union increasingly focuses on expanding the scope of works protected by intellectual property rights, including literary works, music, films, and phonograms. The breakthrough in artificial intelligence (AI) has contributed significantly to creating works of art with little or no human intervention. The article examines the current situation of EU copyright law and Vietnamese law regarding AI-generated works. The article concludes that EU law governs copyright for these works based on the extent of human contribution to the creation of the work. Meanwhile, Vietnamese law still needs to resolve the issue of intellectual property rights for works created by AI.